Stop n kobab stall / Muhammad Hakimie Md Mokhtar ...[et al.] - Md Mokhtar, Muhammad Hakimie; Ahmad Zulfaqar, Muhamad Iskandar; Ahmad Zahid, Esqandarhaiqal; Zaini, Muhammad Redzuan (2023)
Stop N Kobab is a place where you can find variation of kebab with a wonderful taste for affordable price for all kebab lover and of course with our priority objective to make every person can fell in love with our kebab. Our primary target is focused in Johor Bahru city area to start our business by targeting a buyer of teenager this food would likely to attract a teenager to taste a thing they never had before. We will take advantage of teenager that will like our food to promote it to social media as teenager nowadays like to make everything that they like viral and we sure with this kind of advantage we can attract a lot of customers to come to our stall. Our business is run by five main job which are general manager, administration manager, financial manager, marketing manager and operation manager. All of us have a significant part to play in this firm, and together we will ensure its success. From our observation we are sure that our business will gain a profit after doing a survey with aspect of competition with other same business, our product quality, price etc. All of that after combined with our marketing strategy, we are sure that our business will become a great success in future by achieve to be a better kebab seller in Malaysia